Link between increased satiety gut hormones and reduced food reward following gastric bypass surgery for obesity - Goldstone,AP; Miras,AD; Scholtz,S; Jackson,S; Neff,KJ; Penicaud,L; Geoghegan,J; Chhina,N; Durighel,G; Bell,JD; Meillon,S; le,Roux CW (Journal of Clinical Endocrinology & Metabolism, 2015)
Context: Roux-en-Y gastric bypass (RYGB) surgery is an effective long-term intervention for weightloss maintenance, reducing appetite, and also food reward, via unclear mechanisms.Objective: To investigate the role of elevated satiety gut hormones after RYGB, we examined foodhedonic-reward responses following their acute post-prandial suppression.Design: Randomised placebo-controlled double-blind cross-over experimental medicine studies.Patients: Two groups, over 5 months after RYGB for obesity (n7–11), compared with non-obesecontrols (n10), or patients after gastric banding (BAND) surgery (n9).Intervention: Studies were performed after acute administration of the somatostatin analogueOctreotide or saline. In one study, patients after RYGB, and non-obese controls, performed abehavioral progressive ratio task (PRT) for chocolate sweets. In another study, patients after RYGB,and controls after BAND surgery, performed a functional magnetic resonance imaging (fMRI) foodpicture evaluation task.Main outcome measures: Octreotide increased both appetitive food reward (breakpoint) in thePRT (n9), and food appeal (n9) and reward system blood oxygen level dependent (BOLD) signal(n7) in the fMRI task, in the RYGB group, but not in control groups.ISSN